VD_FINDINFO HC / 2014 / 892 vom 20. Oktober 2014 - VD Tribunal cantonal (2014)
OBLIGATION D'ENTRETIEN, RÉPARTITION DES FRAIS | 279 al. 1 CC, 285 al. 1 CC, 106 al. 1 CPC (CH), 107 al. 1 let. a CPC (CH)